Range control MPC with application to Vapor Compression Cycles. (March 2020) - Prášek, Jan; Trnka, Pavel; Havlena, Vladimír; McGahan, Paul
Abstract: A range control MPC formulation is presented for control of Vapor Compression Cycles (VCC). Variation in system dynamics is handled through application of range control which is a generalization of a tracking problem whereby the set-point for the system output is replaced by a funnel (time-varying upper and lower bounds on the system output) which is implemented as a set of soft constraints. Vapor cycle is optimized to maximize device efficiency while ensuring feasibility of operation. Experimental validation of the control design, embedded in a heat-pump controller, is presented. Highlights: Steady state optimization of vapor compression cycles with modulating components. Multivariable model predictive control for vapor compression cycles. Robust and calm control with range control strategy and disturbance observer. Lumped parameter vapor compression cycle components modeling.